PENURUNAN PREVELENSI HIPERTENSI SEBAGAI SILENT KILLER MELALUI EDUKASI KESEHATAN DI MASYARAKAT RT 27 DUSUN WONOCATUR BANGUNTAPAN BANTUL - Baiq Qatrunnada Hariyanti; Yuniar Wardani; Muhammad Miftah Rais; Adam Syahputra; Angelika Wahyuni; Hana Nabilah Siti; Alby Rozalvino Fitrajaya (Universitas Muhammadiyah Surakarta, 2026)
Hypertension is a non-communicable disease that can cause serious complications if not controlled early on. Low public awareness of earlyvdetection is the basis for implementing this community service activity in RT 27, Wonocatur Hamlet. The activity aimed to increase residents' knowledge and awareness of hypertension prevention through health education. The methods used were interactive counseling with posters, as well as evaluation using pre-tests and post-tests consisting of 15 questions for 40 participants. The material covered the definition of hypertension, risk factors, and prevention efforts through a healthy lifestyle and regular blood pressure checks. The results showed an increase in participants' knowledge after the intervention and found that 20% of residents had blood pressure ≥140/90 mmHg. Community -based education proved effective in increasing awareness of hypertension control efforts at the community level.